Rebuilding Leviathan : Party Competition and State Exploitation in Post-Communist Democracies - Busse, Anna Grzymala (Cambridge University Press, 2013)
The ideas for this book first sprouted at the “Rethinking the Post- Communist State” conference Pauline Jones Luong and I organized at Yale University in 2001. They grew as parts of this manuscript were presented at the University of California-Berkeley, the University of Chicago, Cornell University, Harvard University, McGill University, the Massachusetts Institute of Technology (MIT), the University of Michigan, the University of Wisconsin-Madison, the World Bank, and Yale University. The careful readers and listeners at these institutions helped me to sharpen the argument and clarify my thinking.